1966
DOI: 10.1111/j.1748-1716.1966.tb03213.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Gastric Inhibitory Substance on Gastric Secretion in the Pylorus Ligated Rat1

Abstract: An extract was prepared from juice secreted by vagally denervated isolated pouches of the gastric antrum in the dog, by dialyzing against water and lyophilization. This gastric inhibitory substance (GIS) was assayed in pylorus ligated rats. Three groups of rats served as controls. One group received no injections, while the two other were injected with saline (1 ml/100 g rat) intravenously (i.v.) or intraperitoneally (i.p.). Two different types of gastric secretion were studied: (a) basal or spontaneous gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1967
1967
1988
1988

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, substances of totally different types have also been reported to have effect. SEMB (1966) found a preparation gained from the antrum of dogs to have a considerable inhibitory effect on Shay rats-a mechanism of action which presumably can be left out of account in the present study. BASS et al.…”
mentioning
confidence: 53%
“…However, substances of totally different types have also been reported to have effect. SEMB (1966) found a preparation gained from the antrum of dogs to have a considerable inhibitory effect on Shay rats-a mechanism of action which presumably can be left out of account in the present study. BASS et al.…”
mentioning
confidence: 53%
“…The doses of the extracts from antrum or fundus were also of the same order of magnitude as those shown previously to give inhibition upon i.v. injection (Semb 1966a(Semb , 1969. I n earlier studies, it was shown that inhibition of gastric acid secretion took place about 3/4-1 hr after the i.v.…”
mentioning
confidence: 98%
“…injection of extracts from gastric juice. Extracts prepared from human anacid gastric juice and juice of isolated antral pouches in the dog are the richest source of this inhibitor (Brunschwig et al 1939, 1940, Hood, Code and Grindlay 1953, Semb 1966a . However, the mode of action of this "gastric inhibitory substance" (GIS) is not clear.…”
mentioning
confidence: 99%
“…Gastrone is the endogenous inhibitor of gastric acid secre tion (9) described by Brunschwig et al (4) in anacid human gastric juice and determined by means of bioassays on dogs with Pavlov pouches. Its inhibitory activity on HC1 output has been thereafter studied by Blackburn et al (2) and Code et al (5) on dogs with Heidenhain pouches and by other authors on rats with pyloric ligation (6,12,13) or gastric fistula (1). Gastrone B is the impor tant inhibitor of hydrochloric acid secretion contained in 'fraction 7' of Fiasse et al (6) separated from the anacid gastric juice on Scphadex G-100 column.…”
mentioning
confidence: 99%